Global economy and digital society - Bohlin, Erik, 1961- (Amsterdam ; London : Elsevier, 2004)
This book deals with the implications of a global economy and the emergence of a society permeated by information and communication technologies. The book includes a special focus on telecommunications markets and policy and on user perspectives. It also represents a holistic approach, bringing to bear a number of critical perspectives: economics, engineering, business, organization theory, psychology, policy analysis, and security concerns.
Papers selected from the 14th International telecommunications Society 14th biennial conference.
Includes bibliographical references and index.
rpm 23/05/13
Loans
Selected papers. Theme title "Challenges and opportunities in the digital century: the role of information and telecommunications".
Keywords: Telecommunication systems -- Economic aspects -- Congresses; Information superhighway -- Congresses; Telecommunication systems -- Congresses; Global economy; Digital society